2022
DOI: 10.1021/acs.est.1c08806
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of Co(OH)2 Nanosheets Growing on the KNbO3 Perovskite Based on Electronic Structure Modulation for Enhanced Peroxymonosulfate Activation

Abstract: Material-enhanced heterogonous peroxymonosulfate (PMS) activation on emerging organic pollutant degradation has attracted intensive attention, and a challenge is the electron transfer efficiency from material to PMS for radical production. Herein, an interface architecture of Co­(OH)2 nanosheets growing on the KNbO3 perovskite [Co­(OH)2/KNbO3] was developed, which showed high catalytic activity in PMS activation. A high reaction rate constant (k 1) of 0.631 min–1 and complete removal of pazufloxacin within 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(65 citation statements)
references
References 60 publications
1
59
0
Order By: Relevance
“…The d-band center level of Fe in Fe 2 CN is −2.54 eV, which was shifted to the Fermi level relative to −4.45 eV in Fe 1 CN and −6.85 eV in Fe n CN. Therefore, a higher d-band center level may indicated that the better activity for the catalytic reaction was attributed to the coupling with the Fe-3d orbits of adjacent Fe atoms. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The d-band center level of Fe in Fe 2 CN is −2.54 eV, which was shifted to the Fermi level relative to −4.45 eV in Fe 1 CN and −6.85 eV in Fe n CN. Therefore, a higher d-band center level may indicated that the better activity for the catalytic reaction was attributed to the coupling with the Fe-3d orbits of adjacent Fe atoms. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a higher d-band center level may indicated that the better activity for the catalytic reaction was attributed to the coupling with the Fe-3d orbits of adjacent Fe atoms. 16,41 Atomic Structure and Chemical State of Fe x CN. The preparation procedure of Fe 1 CN and Fe 2 CN is illustrated in Figure 2a,b.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5,6 For example, Liu et al constructed an interface architecture by growing Co(OH) 2 nanosheets on the KNbO 3 perovskite and achieved high catalytic activity for peroxymonosulfate activation. 7 Zhang et al discovered that a unique Co 3 O 4 /TiO 2 p–n heterojunction with interface defects could induce the improvement of oxygen mobility and the generation of surficial reactive oxygen, thus accelerating the photothermal catalytic degradation of toluene. 8 Liu et al reported a high-efficiency monolithic catalyst with interfaces by in situ growth of MOFs, and it was found that the interfacial interaction could accelerate the fracture of the Co–O bond, which is beneficial to molecular oxygen activation and acetone oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has to introduce external activation factors including heat, 6 alkaline conditions, 7 and homogeneous 8,9 and heterogeneous catalysts. [3][4][5][10][11][12][13][14][15] Among them, a heterogeneous catalyst for the activation of PMS is a good strategy for repeated use, realization of radical and non-radical routes, etc. The activation of PMS by heterogeneous catalysts containing defect sites has attracted much attention in the past few years.…”
Section: Introductionmentioning
confidence: 99%